Exploring the relationship between super bowls and potential online sex trafficking - Huang, Xi (Trends in organized crime, 2024)
Sex trafficking is one type of human trafficking, which involves scenarios where individuals are not paid and are forced to engage in forced sex, forced prostitution, and sexual slavery. Online advertising is increasingly used by traffickers as an anonymous and efficient method to exploit victims. Large sporting events have been linked to increases in sex trafficking, although there is limited empirical evidence to support this claim. The goal of this study is to answer the following question: What is the relationship between Super Bowls and potential online sex trafficking? Using time series Poisson analysis of secondary data on online sexual service advertisements in Florida during the 2020 and 2021 Super Bowls, which took place in Miami and Tampa, Florida, respectively, the result indicates an increase in online advertisements that exhibit indicators of sex trafficking during the two Super Bowls. The paper concludes by providing recommendations for federal, state, and local law enforcement for improving sex trafficking responses during large sporting events and outlines a future research agenda on the relationship between large sporting events and sex trafficking.